Optimal switch allocation for automatic load transfer in distribution substations - Viotto Romero, M. E.; Wesz Da Silva, L. G.; Mantovani, J. R S [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This work proposes a methodology for optimized allocation of switches for automatic load transfer in distribution systems in order to improve the reliability indexes by restoring such systems which present voltage classes of 23 to 35 kV and radial topology. The automatic switches must be allocated on the system in order to transfer load remotely among the sources at the substations. The problem of switch allocation is formulated as nonlinear constrained mixed integer programming model subject to a set of economical and physical constraints. A dedicated Tabu Search (TS) algorithm is proposed to solve this model. The proposed methodology is tested for a large real-life distribution system. © 2011 IEEE.
Keywords: Distribution Systems; Reactive Tabu Search; Reliability; Restoration; Distribution substations; Distribution systems; Load transfer; Mixed integer programming model; Optimal switch; Optimized allocation; Physical constraints; Radial topology; Reactive Tabu search; Reliability index; Switch allocations; Tabu search algorithms; Transfer loads; Computer programming; Image reconstruction; Integer programming; Local area networks; Sustainable development; Tabu search